Peningkatan Mutu Pendidikan sebagai Pilar Utama Peningkatan Daya Saing Nasional Indonesia di Era Globalilasi - Taryanto; Suwito Eko Pramono (CV. Lenggogeni Data Publishing, 2026)
Improving the quality of education is a key pillar in building Indonesia’s national competitiveness in the era of globalization. Education plays a strategic role as the foundation for developing high-quality, innovative, and strong-character human resources. Investment in education not only benefits individuals but also contributes to social stability, economic growth, and competitiveness in the global market. However, the quality of education in Indonesia continues to face several challenges, including regional disparities, the limited relevance of curricula to industry needs, and weak character and mentality as reflected in persistently high levels of corruption. To address these challenges, comprehensive reforms are required, including strengthening competency-based curricula, improving teacher professionalism, implementing Total Quality Management (TQM) through PDCA and the Juran Trilogy, and developing higher education institutions toward becoming research universities. In addition, enhancing community participation is essential to ensure democratization, transparency, and accountability in education governance. Collaboration among the government, private sector, and society through the Triple Helix model will further strengthen innovation and the relevance of education to the labor market. Education must also focus on character development, digital literacy, and 21st-century skills to meet global dynamics. Ensuring equitable access to quality education across all regions of Indonesia is a priority to maximize the demographic dividend. Through policy synergy, institutional capacity strengthening, and active involvement of all stakeholders, Indonesia can build an inclusive, adaptive, and globally competitive education system.